Refractive errors in type II diabetic patients - Shrestha, Shristi; Kaini, Khem Raj (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: The prevalence of diabetes is increasing rapidly. Refractive error in the diabetic population is considered a main cause of visual impairment. So this study was conducted to find out the pattern of refractive errors in patients with type II diabetes mellitus in Western Nepal. MATERIAL AND METHODS: It was a hospital-based cross-sectional study. Three hundred forty eyes of one hundred seventy patients with type II diabetes underwent comprehensive eye examination including subjective and objective refraction and serum biochemistry. RESULTS: The mean refraction was -0.132±0.88 D. Emmetropia was seen in 49.7% of the patients, hypermetropia in 22.6%, myopia in 12.6%, and astigmatism in 15% of the patients. Older age groups had more hypermetropic refractive error (p<0.05). Female gender was a risk factor for hypermetropia (p=0.042). Good glycemic control was seen in 49.7%. There was statistically significant correlation between fasting blood sugar level and spherical equivalent refraction (p<0.05, r = -0.115). CONCLUSION: The present hospital-based study noted a refractive error in 50.3% among diabetic population in Pokhara with hypermetropia being the most common type (22.6%) than myopia (12.6%) and astigmatism (15%).